Digital Cash Waqf and Legal Transformation in Indonesia: Harmonizing Islamic Philanthropy with Positive Law - Qorri Maftukhah; Latazalina Aisyah Nahdoh (Khuluqiyya: Jurnal Kajian Hukum dan Studi Islam, 2026)
The rapid development of financial technology has transformed the management and distribution of Islamic philanthropic instruments, including cash waqf in Indonesia. Digital cash waqf has emerged as an innovative mechanism that enhances accessibility, transparency, and public participation in waqf practices through online platforms and financial technology systems. This study examines the legal transformation of digital cash waqf in Indonesia by analyzing the relationship between Islamic law principles and the national positive legal framework governing waqf management. Using a normative juridical approach combined with conceptual and statutory analysis, this research explores the harmonization between Sharī‘ah principles, Law Number 41 of 2004 concerning Waqf, and contemporary financial regulations related to digital transactions and fintech governance. The findings demonstrate that digital cash waqf possesses significant potential to strengthen Islamic social finance, promote financial inclusion, and support sustainable socio-economic development. Nevertheless, challenges remain regarding legal certainty, institutional supervision, digital literacy, cybersecurity, and Sharī‘ah compliance in digital waqf operations. The study argues that strengthening regulatory integration and adaptive legal governance is essential to optimize digital cash waqf in Indonesia. Furthermore, collaboration between state institutions, Islamic authorities, and financial technology providers is necessary to ensure accountable, transparent, and sustainable digital waqf management within the national legal system.